The Escherichia coli Growth Inhibition Activity of Some Fermented Medicinal Plant Leaf Extract from the Karo Highland, North Sumatra (Biodiversitas Journal of Biological Diversity, 2009)
A lot of traditional medicinal plant has antibacterial activities. Most of these plants are freshly chewed or grounded and useddirectly to treat infectious bacterial diseases. However, some practices employ a traditionally spontaneous fermentation onboiled extracted leaf, root or other parts of the plant. This work reports a laboratory stimulated spontaneous fermentation of leaf extracts from selected medicinal plants collected from the Karo Higland. The spontaneous fermentation was stimulated to be carried out by the Acetobacter xylinum and Saccharomyces cerevisiae. The anti-infectious agent activity was assayed on the Escherichia coli growth inhibition. A complementary non fermented leaf extract was also made and assayed as a comparative measure. Indeed, the fermented leaf extract of bitter bush (Eupatorium pallescens), cacao (Theobroma cacao),avocado (Persea gratissima), passion fruit (Passiflora edulis), cassava (Cassava utilissima), diamond flower (Hedyotis corymbosa), periwinkle (Catharanthus roseus), and gandarussa (Justicia gendarussa) have relatively higher anti-E. coli activity than those of non fermented ones. However, there were no anti-E. coli activity was detected in both fermented and non fermented leaf extract of the guava (Psidium guajava) and common betel (Piper nigrum).
Keywords: medicinal plant, anti-bacteria, Escherichia coli, fermentation, Acetobacter xylinum, Saccharomyces cerevisiae.